2023
DOI: 10.3390/ijms24043144
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Trypanosoma congolense and T. vivax Nucleoside Transporters Reveal the Potential of P1-Type Carriers for the Discovery of Broad-Spectrum Nucleoside-Based Therapeutics against Animal African Trypanosomiasis

Abstract: African Animal Trypanosomiasis (AAT), caused predominantly by Trypanosoma brucei brucei, T. vivax and T. congolense, is a fatal livestock disease throughout Sub-Saharan Africa. Treatment options are very limited and threatened by resistance. Tubercidin (7-deazaadenosine) analogs have shown activity against individual parasites but viable chemotherapy must be active against all three species. Divergence in sensitivity to nucleoside antimetabolites could be caused by differences in nucleoside transporters. Havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 105 publications
(225 reference statements)
0
15
0
Order By: Relevance
“…Because the nitrofuranylazines showed the best trypanocidal activity against the animal trypanosome T. congolense IL3000 (Figure 2), structure−activity relationships (SARs) were observed relative to the said trypanosome. Differences in drug sensitivity may result from variances in the parasites' capacity to internalize, 59 activate, 60 and/or metabolize 61 drug candidates. Moreover, based on the promising in vitro trypanocidal activity and selectivity of derivatives 4a, 7a, and 8b (Table 2), these azines were selected for in vivo treatment efficacy assessment in T. congolense IL3000 infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…Because the nitrofuranylazines showed the best trypanocidal activity against the animal trypanosome T. congolense IL3000 (Figure 2), structure−activity relationships (SARs) were observed relative to the said trypanosome. Differences in drug sensitivity may result from variances in the parasites' capacity to internalize, 59 activate, 60 and/or metabolize 61 drug candidates. Moreover, based on the promising in vitro trypanocidal activity and selectivity of derivatives 4a, 7a, and 8b (Table 2), these azines were selected for in vivo treatment efficacy assessment in T. congolense IL3000 infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition patterns of P1 and P2 will be further described in the drug development sections. Interestingly, T. congolense and T. vivax that cause animal trypanosomiasis lack P2 altogether and have only one major P1 transporting activity in each species (Ungogo et al 2023 ). The single T. congolense P1 transporter is called Tco AT1 or Tco NT10 (not to be confused with Tb AT1 from T. brucei , which is a P2 transporter), and the only T. vivax P1 transporter that could be confirmed to be active is called Tvx NT3.…”
Section: Nucleoside and Nucleobase Transportmentioning
confidence: 99%
“…Transport studies showed that both Tco AT1 and Tvx NT3 are purine-specific and recognize typical P1 substrates (adenosine, inosine, and guanosine), but Tvx NT3 has a broader substrate specificity and can also bind purine nucleobases (not tested as substrates). Similarly to the T. brucei P1 transporters (but unlike P2), Tco AT1 and Tvx NT3 does not seem to transport drugs tested from the diamidine and melanophenyl arsenical families (Munday et al 2013 , Ungogo et al 2023 ). In addition to the purine nucleoside transporters, all three species have several genes encoding purine nucleobase transporters, although they have only been characterized in T. brucei .…”
Section: Nucleoside and Nucleobase Transportmentioning
confidence: 99%
“…This system provides an ideal null background for the expression and characterization of single equilibrative nucleoside transporter (ENT) genes. Using the same null background Leishmania mexicana cell line, in the manuscript “Cloning and Characterization of Trypanosoma congolense and T. vivax Nucleoside Transporters Reveal the Potential of P1-Type Carriers for the Discovery of Broad-Spectrum Nucleoside-Based Therapeutics against Animal African Trypanosomiasis” Ungogo et al [ 7 ] investigated the druggability of the main adenosine transporters (purine nucleoside transporter NT3) of T. vivax (TvxNT3) and T. congolense (TcoAT1/NT10) by 7-substituted tubercidins and other nucleoside analogs. They showed that chemotherapy for Animal African Trypanosomiasis is possible.…”
Section: Original Research Workmentioning
confidence: 99%